New Perspective On Governance Leadership Conflict And Nation Building In Sierra Leone - Berewa, Solomon (Bloomington AuthorHouse, 2011)
Sierra Leone is in her final phase of a Post-civil War rebuilding after twelve years of what has been dubbed one of the most devastating civil conflicts in Modern African History. Since the advent and end of the conflict a lot has been written in the forms of documentaries, reportages, commentaries, satires and academic textbooks by journalists, academics, politicians, former heads of state and political analysts. However, this book- `A New Perspective On Governance, Leadership, Conflict and Nation Building in Sierra Leone'. is different. It presents a new outlook in the sense that it is incisive, analytical, honest, educative and thought-provoking at the same time. The key message that runs through the veins of the theme is state renewal informed by new thinking spectacles that efficiently configure the manner in which the management of state leadership and governance is articulated for the benefits of the common good. The author, Solomon E. Berewa was one of the key actors- Chief Government Negotiator and stakeholder of the peace deals in his capacity as Minister of Justice and Attorney General and Vice President of the Republic of Sierra Leone. He has written this masterpiece authoritatively by throwing fresh lights on the serious political issues and questions which have blurred the significance of the past and the present. Like any sincere agent of nation building, after a traumatic experience such as the one Sierra Leone went through, the rationale of the author is to build bridges across the board, political spectrums. In his estimation, it is only by looking into the past with open mind and sincerity, learn tangible lessons and act on them meticulously, that nations can be in position to surmount current challenges for the good and durability of a better tomorrow. Post-war Sierra Leone needs to have faith in this philosophy and crown it as the cornerstone in this crucial period of political and socio-
Keywords: Sierra Leone